Legal and cultural differences in medical decision-making on behalf of very young children - Goold, I; Auckland, C (Hart Publishing, 2020)
This collection brings together analyses of disputes between parents and doctors over the treatment of seriously ill young children from more than twenty-five jurisdictions across six continents. While it is impossible to do justice to all of the themes or patterns that emerge from the contributors in this book, in this chapter, we hope to draw out some of the key themes, and to contextualise these within the social and cultural background of the countries discussed. We begin by exploring the reasons for the lack of reported case law in many of the jurisdictions, which may be explained both by some countries’ values being less likely to give rise to conflict in the first place, and by the existence of alternative mechanisms for resolving such disputes which avoid an adversarial court process. We go onto consider how the role of parents in such decisions are conceptualised, and the differing limits placed of parental authority in the countries examined, with different thresholds to be met before the court can become involved and override a parent’s decision. Finally we examine differences in how the courts in different countries are applying common standards such as ‘best interests’, and the challenges they face in doing so.